The Connection Gaps in Vietnam’s Innovation Startup Ecosystem: Insights into the Role of Research, Intellectual Property, Technology Transfer, and Innovation Organizations - Minh Ngoc, Nguyen; Thi Lien Huong, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 41 No 3DO - 10.25073/2588-1116/vnupam.4572, 2025)
This paper analyzes the connectivity gaps in Vietnam’s innovation startup ecosystem, focusing on four groups of organizations involved in knowledge creation, management, and transfer: R&D, intellectual property, technology transfer, and innovation organizations. Based on a three-dimensional analytical framework, internal capacity, level of connectivity, and ecosystem impact, the study identifies systemic bottlenecks and proposes four groups of policy solutions to enhance the coordinating, integrative, and knowledge-diffusion roles of these organizations within the national innovation startup ecosystem.